How we write : writing as creative design - Sharples, Mike, 1952- (Routledge, 1999)
"How We Write is an accessible guide to the entire writing process, from forming ideas to formatting text. Combining new explanations of creativity with insights into writing as design, it offers a comprehensive account of the mental, physical and social aspects of writing." "How We Write explores how children learn to write; creativity and idea generation; the processes of planning, composing and revising; the visual design of text; the cultural influences on writing; and the future of writing and the creation of a global hypertext." "Mike Sharples illustrates the habits, strategies and techniques of successful (and unsuccessful) writers through a wealth of examples."--Jacket